Proceedings of the 3rd International Conference on Innovative Research Across Disciplines (ICIRAD 2019) 2020
DOI: 10.2991/assehr.k.200115.012
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions of the Utilization of ICT in English Learning: Way or Barrier?

Abstract: This study aimed to describe the students' perceptions of the utilization of ICT in English learning. One hundred and thirty-four students of a private university in South Sumatera were involved as participants of this study. The questionnaires were administered to gain a portrait of students' perceptions. Based on the findings, it was figured out that ICT promoted learning activity, maintained learning motivation, and increased learning achievements. However, ICT potentially hindered students' focus and expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…In addition, due to the exhaustive amount of data and information available online, more than half of the participants felt that it was difficult to find suitable learning materials from the wide ocean of resources. Similar findings were recorded by Irzawati and Hasibuan [23], where the participants perceived the possibility of misusing of data.…”
Section: Students' Perceptions On the Online Resourcessupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, due to the exhaustive amount of data and information available online, more than half of the participants felt that it was difficult to find suitable learning materials from the wide ocean of resources. Similar findings were recorded by Irzawati and Hasibuan [23], where the participants perceived the possibility of misusing of data.…”
Section: Students' Perceptions On the Online Resourcessupporting
confidence: 84%
“…Similarly, 75% of the participants accepted that online activities were interesting and motivated them to learn English. Similar findings by Aljumah [18] and Irzawati and Hasibuan [23] confirm the positive perceptions of students on utilizing the online resources in learning English. The study further revealed that the students expect their language teachers to incorporate web-based activities in their teaching.…”
Section: Students' Perceptions On the Online Resourcessupporting
confidence: 74%
See 1 more Smart Citation
“…This technique promoted learning activity maintained the students' learning motivation and increased speaking achievement using ICT. It is contrary to Hasibuan in [26] that said the students' perceptions of utilizing ICT in English learning potentially distracted the students' focus and caused data misuse.…”
Section: The Students' Positive Response Toward the "Dr Ecrip-ict" Based Techniquementioning
confidence: 88%
“…However, integrating ICT is crucial for enhancing academic procedures in vocational education (Aryani & Siahaan, 2020). ELT aims to enhance students' English language competency, and since technology can aid language learners, it should play a significant role in their academic pursuits (Irzawati & Hasibuan, 2020). Therefore, understanding students' perceptions regarding ICT integration in ELT in vocational schools is essential.…”
Section: Introductionmentioning
confidence: 99%